The influence of ethnicity and culture on the valuation of environmental improvements: Results from a CVM study in Southwest China - Michael Ahlheim; Tobias Börger; Oliver Frör (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2013)
The provision of environmental goods by government creates social benefits which might vary between citizen groups with different cultural and ethnic backgrounds. These differences as well as the overall extent of benefits should be analysed before the implementation of public projects in order to consider not only the efficiency aspects of such a project but also its distributional effects. In Southwest China we are facing a rapid deforestation for the development of rubber cultivation and at the same time find an ethnically highly diverse population. This Contingent Valuation study tries to assess the short-term and long-term benefits accruing from a public reforestation programme in Xishuangbanna and their distribution among different ethnic groups living in that region. The results show that different ethnic groups value short-term and future benefits of reforestation differently and that these differences can be explained by the different cultural and historical backgrounds of these ethnic groups.
urn:nbn:de:bsz:100-opus-8872
Keywords: D31; D33; E6; E25; 330; Rubber cultivation; contingent valuation method; environmental costs; ethnicities; equity; cultural ecosystem services; China